The Influence Of Lactation Management And Lactation Smart Book On Breasfeeding Success - Yanyan Mulyani Yanyan; Dewi Nurlaela Sari; Linda Rofiasari3 (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2022)
Intensive lactation management is an effort by mothers and families to support successful breastfeeding. This management includes the preparation and counseling of mothers, breastfeeding practices and inpatient care, as well as ongoing efforts for mothers to breastfeed. Mother's Milk (ASI) is the best natural nutrition for babies because it contains the energy and substances that babies need for the first 6 months of life. The World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) recommend that mothers breastfeed from the first hour of life until the age of 6 months. The purpose of the study was to determine the effect of lactation management and lactation smart books on the success of lactation in postpartum mothers. The study used a quasi-experimental design without control, a pretest, lactation management treatment and smart books and posttest were carried out. Sampling using accidental sampling technique. The research sample was all postpartum mothers from 0-7 days as many as 30 people. The results of the bivariate analysis of the study using the Wilcoxon signet rank test before and after showed a significant difference with the average before 2.0000 with a standard deviation of 1.05045 and after showing an average value of 3.6333 with a standard deviation of 0.49013, the results of statistical tests found that there was an influence on lactation management and books. smart lactation with successful breastfeeding with a p value of 0.000. Keywords: Lactation Management, Smart Books, Breastfeeding Success